Pelatihan Pembuatan Teh Bunga Rosella Sebagai Produk Rumahan di Desa Sungai Merdeka - Fadilla, Raisa; Aryanti, Fika; Indriyanti, Niken; Sinthary, Venna; Jafar, Fahriani Istiqamah; Kurniawan, Hery; Aryatika, Karera; Firmansyah, Ganjar; Anshory, Jamil (Jurnal Pengabdian Masyarakat (ABDIRA), 2023)
In various studies, rosella flowers can cure various diseases, prevent disease transmission and are used as processed food or health drinks. The increasing use of rosella flowers can be a business opportunity and can improve the community's economy, but limited knowledge, skills, abilities, creativity, innovation and inadequate guidance are obstacles to the community in utilizing rosella, so training is needed to increase people's knowledge and skills in utilizing rosella. and home product development. The purpose of carrying out this activity is to increase public knowledge about rosella plants, how to make rosella flower tea and how to increase the economic value of a product. This activity was carried out using the training method, beginning with the provision of material on rosella and how to increase the economic value of a home product, followed by direct demonstrations and practice of making rosella flower tea. This activity is useful for increasing public knowledge regarding rosella plants, the use of rosella flowers, how to make rosella flower tea and how to increase the economic value of a home product.